Amorphous Calcium Carbonate Granules Form Within an Intracellular Compartment in Calcifying Cyanobacteria - Blondeau, Marine; Sachse, Martin; Boulogne, Claire; Gillet, Cynthia; Guigner, Jean-Michel; Skouri-Panet, Fériel; Poinsot, Mélanie; Ferard, Céline; Miot, Jennyfer; Benzerara, Karim (Frontiers in Microbiology, 2018)
The recent discovery of cyanobacteria forming intracellular amorphous calcium carbonate (ACC) has challenged the former paradigm suggesting that cyanobacteria-mediated carbonatogenesis was exclusively extracellular. Yet, the mechanisms of intracellular biomineralization in cyanobacteria and in particular whether this takes place within an intracellular microcompartment, remain poorly understood. Here, we analyzed six cyanobacterial strains forming intracellular ACC by transmission electron microscopy. We tested two different approaches to preserve as well as possible the intracellular ACC inclusions: (i) freeze-substitution followed by epoxy embedding and room-temperature ultramicrotomy and (ii) high-pressure freezing followed by cryo-ultramicrotomy, usually referred to as cryo-electron microscopy of vitreous sections (CEMOVIS). We observed that the first method preserved ACC well in 500-nm-thick sections but not in 70-nm-thick sections. However, cell ultrastructures were difficult to clearly observe in the 500-nm-thick sections. In contrast, CEMOVIS provided a high preservation quality of bacterial ultrastructures, including the intracellular ACC inclusions in 50-nm-thick sections. ACC inclusions displayed different textures, suggesting varying brittleness, possibly resulting from different hydration levels. Moreover, an electron dense envelope of ~2.5 nm was systematically observed around ACC granules in all studied cyanobacterial strains. This envelope may be composed of a protein shell or a lipid monolayer, but not a lipid bilayer as usually observed in other bacteria forming intracellular minerals. Overall, this study evidenced that ACC inclusions formed and were stabilized within a previously unidentified bacterial microcompartment in some species of cyanobacteria.